FORMATION OF A DIGITAL EDUCATION MODEL IN TERMS OF THE DIGITAL ECONOMY (BASED ON THE EXAMPLE OF EU COUNTRIES) - Oksana Buhaichuk; Vitalina Nikitenko; Valentyna Voronkova (Baltic Journal of Economic Studies, 2023)
The relevance of the study is that the digital challenge is important and stimulating, requiring the formation of digital education in the digital economy. The purpose of the article is to develop a model of digital education as a factor of improving the efficiency of digital competencies that contribute to the development of the digital economy. The object of research is the formation of a digital education model as a factor in the implementation of digital literacy. The subject of the study is the impact of the digital education model on the development of the digital economy. The methodology for researching digital education, which cultivates a smart economy, smart governance and smart people, is represented by the Agile methodology (flexible adaptive), based on the use of the values of artificial intelligence and deep learning, which can create effective tools for education, increasing their effectiveness through rapid change. The results of the study: 1) analyzes the formation of digital competencies in the context of the European educational paradigm that contribute to the development of the digital economy; 2) identifies the directions of implementation of digital competencies in the context of the European educational paradigm; 3) reveals digital tools and educational platforms that contribute to the formation of digital education; 4) formulates the concept of quality, inclusive, accessible digital education as a factor in improving digital competencies and adapting education to the digital age; 5) traces the impact of digital education and digital competencies on the development of the digital economy. The concept of digital education contains both its potential and its risks, which can have serious consequences for the future of the educational process if digital literacy is not developed. The combination of four factors – cultural change, technological innovation, national policy leadership and internal development of the digital education system – stimulates the digital transformation of society.